Features of the application of punishment medical criminal offenses - N. Jetibayev; A. Amankeldi (Halyk̦aralyk̦ k̦atynastar ža̋ne halyk̦aralyk̦ k̦u̇k̦yk̦ seriâsì, 2018)
The use of punishment to the convict by court order is nothing more than, as the implementation of the specific nature and size of the criminal liability established by the court in accordance with the criminal law in the science of criminal law throughout its development a lot of attention was paid to the problems of scientists punishment. Punishment, pursuing the goal of special and general prevention is the punishment for the crime committed. The main social function of punishment should be considered its preventive function that is included as part of the measures in the fight against crime. At the same time we can not ignore the specifics of reckless criminal who has in most cases, higher value systems than intentional criminal. This feature should determine punishment in sentencing for crimes of negligence is necessary and should take into account the properties collectively characterize the personality of the offender. Therefore humanization trends in the evaluation of properties of the person who commits an act of negligence, is correct. This is to be welcomed in the judicial practice everywhere. In general, extreme measures are already struggle with medical criminal offenses is the application of criminal penalties. The main part of medical criminal offenses related to the categories of small and medium gravity, providing alternative sanctions. Key words: punishment, medical criminal offenses, fines, imprisonment, arrest.